“All scenarios are wrong, but some are useful”—Toward a framework for assessing and using current climate risk scenarios within financial decisions - Baer, Moritz; Gasparini, Matteo; Lancaster, Ryan; Ranger, Nicola (Frontiers in Climate, 2023)
In response to a growing awareness of the potential impact of climate change on financial stability, academics, financial institutions (FIs), central banks and supervisors have developed a suite of scenarios and analytical tools to assess forward-looking climate-related financial risks, inform macro-prudential policies and firm-level risk management and business planning decisions. Climate scenario analysis brings new challenges versus traditional scenario analysis by financial institutions, particularly given the limitations, uncertainties and trade-offs inherent in the data, models and methods for such climate financial risk assessments. We argue that all scenarios are wrong, but this does not necessarily mean that they cannot be useful if used and expanded upon with full awareness of the limitations. In this paper, we explain those limitations in the context of the specific requirements by FIs for scenario analysis and propose an approach to scenario construction and expansion to complement existing scenarios and increase their suitability for decision making for key financial use cases. Importantly, we argue that current scenarios are likely closer to the lower end of the range of plausible future risk for both physical and transition risk. This has implications for both stress testing and risk management, and business planning. We advocate for harnessing the full breadth of scenario narratives to avoid the accumulation of systemic risks and our framework provides an initial step toward this. Finally, we call for FIs, Central Banks and research institutions to work more closely together to develop a more comprehensive scenario taxonomy to help navigate the implications of material financial risk under uncertainty.